Estrategias para implementar la producción de jugo de caña de azúcar envasado en vidrio que impulse el desarrollo socioeconómico de los habitantes de la parroquia La Victoria del cantón Salitre, provincia del Guayas - Escobar Vivar, Gabriela (2015)
The implement an innovative strategy for the inhabitants of the parish "La Victoria", it makes the development of this research project viable. Get the sugar cane juice in glass and then package it and market it makes is made and economically develop the livelihoods of the inhabitants of this rural parish in the province of Guayas, which essentially has devoted a lifetime to produce sugar cane by hand. First, the problem of implementation of the research project, together with the research problem, ie addresses, limiting that inhabitants, scarce resources, dependency on weather conditions, trade policies affecting production sugar cane, among others…….